High temperature nanotribology of ultra-thin hydrogenated amorphous carbon coatings. (October 2017) - Zhang, Youfeng; Polychronopoulou, Kyriaki; Humood, Mohammad; Polycarpou, Andreas A.
Abstract: The present study utilizes a high-temperature nano-mechanical system to perform shallow tribology experiments on an ultra-thin (3 nm) hydrogenated amorphous (a-C:H) coating at elevated temperatures up to 300 °C. The nano-scratch experiments (single scratch) provide in-situ measurement of the friction coefficient and material deformation of the carbon film. The nano-wear experiments (repeated scratches over an area) investigate the extent of wear under multiple scratches. The two groups of experiments reveal the temperature dependence of the tribological behavior of the coating. Raman analysis is performed to compare the chemical structure of the carbon film before and after heating. The spectrum reveals both the hydrogen and sp 3 content of the carbon film decrease after the high-temperature experiments, which contribute to deterioration of the wear resistance of the coating. Graphical abstract: